"The following articles for this Special Issue were published before this collection was released. They can be found in their respective issues or online.". Issue 4 (28th February 2022) - Unknown
Abstract : Volume 36, Number 6 Determining the location of isolation hospitals for COVID‐19 via Delphi‐based MCDM method Nezir Aydin and Sukran Seker https://doi.org/10.1002/int.22410 Volume 36, Number 9 Optimization of electric vehicles charging station deployment by means of evolutionary algorithms Alessandro Niccolai, Leonardo Bettini and Riccardo Zich https://doi.org/10.1002/int.22515